Intensidade da Coloração Verde Foliar em Genótipos de Coffea Canephora: Diversidade Genética e Relação Com o Desempenho Fotossintético - Silva, Angelica Tomazeli da (2020)
The selection of genotypes with superior photosynthetic performance is essential to obtain significant gains in breeding programs, since understanding the physiological aspects of coffee, reflected in photosynthetic performance, can contribute to increasi